2008
DOI: 10.3844/ajassp.2008.1650.1661
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Wash Performance Analysis of Microbial Extracellular Enzymes from East Calcutta Wetland in India

Abstract: Extracellular protease from a novel bacterial isolate showing maximum similarity of 98.22% with Microbacterium luteolum was obtained from East Calcutta Wetland, India. It showed compatibility with commercial detergents. The enzyme retains more than 60% of its activity between 6.0 to 10.5 pH. The maximum activity is at pH 7.5 with 71% activity at pH 10.0 and 10.5. The protease retained its activity between 4 to 60°C with maximum activity at 30°C and a residual activity of 74.4% at 60°C after overnight incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Using Azocasein as a substrate, effect of temperature and pH on the activity of extracellular protease of the isolate was determined by the method mentioned by (Malathu et al, 2008). One unit of activity was defined as the amount of enzyme required to produce an increase of 0.1 absorbance (OD at 440 nm).…”
Section: Determination Of Enzyme Activitymentioning
confidence: 99%
“…Using Azocasein as a substrate, effect of temperature and pH on the activity of extracellular protease of the isolate was determined by the method mentioned by (Malathu et al, 2008). One unit of activity was defined as the amount of enzyme required to produce an increase of 0.1 absorbance (OD at 440 nm).…”
Section: Determination Of Enzyme Activitymentioning
confidence: 99%
“…Wash performance analysis was performed using extracellular protease from individual isolates as per the protocol of Malathu et al (2008). Among the six isolates, extracellular protease from isolate SM2 showed better cleaning efficiency (data not shown).…”
Section: Wash Performance Analysismentioning
confidence: 99%
“…To get the continuous supply of enzymes, SV1 was immobilized on two type of inert matrices; corrugated sheet as well as hay. Protease was estimated by azocasein method as reported by Malathu et al (2008) and amylase production was calculated by DNS method as reported by Anto et al (2006). Enzyme production at regular intervals of 1 h was compared for immobilized matrix (hay as well as sheet) and shake flask culture (incubated at 37°C with continuous shaking at 150 rpm).…”
Section: Continuous Production Of Enzyme By Immobilization On Inert Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, its positional advantage and a wide variety of large habitat conditions with various resources have made it a natural incubator for the growth of huge variety of microbes. A little of its microbial diversity has been explored till now Ghosh et al, 2007;Adarsh et al, 2007;Roy et al, 2008;Malathu et al, 2008, Nasipuri et al, 2010, Riley, 2011Yadav et al, 2010, Mukherjee, 2005Thatoi, 2011; http://indiaenvironmentportal.org.in/node/34248; http://indiaenvironmentportal.org.in/node/14389).…”
Section: Introductionmentioning
confidence: 99%